International politics in an era of democratic peace: the enduring quality of Waltzian structural realism - Coetzee, Eben (University of the Free State, 2017)
International politics continue to be marked (or, more properly) marred by debilitating continuities. Across time and space, and against the vogue of inside-out explanations of international politics (with democratic peace theory as the example par excellence), the study points toward the enduring quality of Waltzian structural realism in theorising and explaining international-political outcomes. The study, accordingly, shows the enduring usefulness of systems theories of international politics and, as against this, the inadequacy of reductionist theories in accounting for international-political outcomes. Waltzian concepts and expectations such as the tyranny of small decisions, balance-of-power theory, emulation and competition, and strange bedfellows are borne out by an examination of the past, present and (as far as possible) future of international politics. The study also shows the lack of empirical and theoretical vindication for democratic peace theory. In making a case for the poverty of democratic peace theory and, as against this, the enduring quality of Waltzian structural realism, the study examines international politics from the period ranging from Ancient Greece to the future of international politics, illustrating that we have much to learn from Waltz’s structural realist theory. Short of the system being transformed, and on account of the evidence presented in this study, Waltzian structural realism is set to remain the basic theory of international politics. In more ways than one, the future of international politics is set to look very much like the past.

Die internasionale politiek word steeds gekenmerk as `n omgewing waarin kontinuït die reël is. Ongeag tyd of ruimte, en teen die heersende drang vir reduksionistiese verklarings van die internasionale politiek (met die demokratiese vredestorie as die voorbeeld by uitstek), dui hierdie studie op die voortdurende relevansie van Kenneth Waltz se teorie van strukturele realisme om die internasionale politiek te verklaar. Voorts wys die studie op die bruikbaarheid van sisteemteorieë van die internasionale politiek en, hierteenoor, die gebrekkige aard van reduksionistiese teorieë ten einde die internasionale politiek te verklaar. Waltz se konsepte en verwagtinge – onder andere, die tirannie van individuele besluite, die magsbalansteorie, nabootsing en kompetisie, sowel as vreemde bondgenote – word deur `n noukeurige ondersoek van die verlede, hede en toekoms gestaaf. Die studie wys ook op die gebrekkige aard van die empirisie en teoretiese grondslag van die demokratiese vredesteorie. Die staaf van Waltz se teorie van strukturele realisme en, hierteenoor, die verwerping van die demokratiese vredestorie, geskied kragtens `n bestudering van die historiese rekord wat strek vanaf Antieke Griekeland tot die toekoms van die internasionale politiek, met die slotsom dat daar allerlei skatte geput kan word uit Waltz se teorie. Met die internasionale politieke sisteem wat steeds gekenmerk word deur anargie, en op grond van die argumente wat in die studie voorgehou is, is Waltz se teorie bestem om die hoeksteen van teoretiese besinning oor die internasionale politiek te bly. Die toekoms, in meer as een opsig, is bestem om bepaalde ooreenkomste met die verlede te toon.
Thesis (Ph.D. (Political Science))--University of the Free State, 2017
Keywords: International relations; Waltz, Kenneth N. (Kenneth Neal), 1924-2013; Realism -- Political aspects